The short-term impact and sustainability of multiple lifestyle interventions on metabolic health and remission of prediabetes and type 2 diabetes: a two-year experience. (11th May 2022) - Iglesies-Grau, J; Dionne, V; Latour, É; Pelletier, V; Bisaillon, M; Tessier, G; Aubut, L; Hamrioui, N; Gagnon, C; Simard, F; Nigam, A; L Allier, PL; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Different intensive lifestyle interventions have been shown to be useful for effective control and even reversal of prediabetes and type 2 diabetes (T2D). Objectives Our heart institute cardiovascular prevention center started a comprehensive lifestyle clinic in 2019 to study the impact of 6 and 12-month non-pharmacological interventions on metabolic health and remission of these two conditions. Methods: Between January 2019 and December 2020, 81 prediabetic (HbA1c ≥ 5.7%) and 184 T2D (HbA1c ≥ 6.5%) were recruited. All participants received regular nutritional counselling (therapeutic moderate carbohydrate restriction Mediterranean diet) and personalized physical exercise prescription (≥30 minutes of moderate aerobic training, 5 times a week, and strength training). Anthropometric measures and fasting blood analysis were measured at 0, 3, 6 and 12 months. Glucose-lowering therapies were not modified, unless necessary. Complete remission of prediabetes and T2D was defined as HbA1c <5.7%, whereas partial remission of T2D was defined as HbA1c <6.5% for at least 3 months, and it was calculated for all the participants that completed the 12-month program. Remission was further evaluated according to pharmacological status (drug-naïve or on glucose-lowering therapy). Results: 231 participants completed the short-term program (87%) and 117 were followed-up to 12 months. Mean age was 67.1 (9.1) years, 67% male, 48.3% with CHD, 53.5% with glucose-lowering therapies. All metabolic health measures were improved, particularly among T2D participants (Table 1). Gains were achieved at 3 months and were maintained during the remainder of the program without significant change. Complete remission of prediabetes was achieved in 24% (95CI: 10.7 to 45.4%) of participants. Complete and partial remission of T2D were achieved in 5.4% (95CI: 2.2 to 12.5%) and 41.3% (95CI: 31.6 to 51.7%) of participants respectively and was observed in both with or without glucose-lowering therapies subgroups (Table 2). Conclusions: Prioritizing lifestyle changes were shown to improve metabolic health measures even to the point of achieving remission among subjects with prediabetes or T2D. These metabolic changes were mostly achieved after 3 months and persisted throughout the intervention. Future research is required to better understand which non-pharmacological interventions work best among subjects with varying metabolic profiles and pharmacotherapy, how long should the interventions last and how partial or complete normalization of glucose impacts long-term outcomes.